2022
DOI: 10.3390/su14137726
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Goals in the COVID-19 Pandemic: A Narrative Review

Abstract: The present narrative review aimed to analyze the impact of the COVID-19 pandemic on the sustainable development goals (SDGS). This information would allow a better comprehension of the actual state of the SDGS and a more efficient programming in future interventions. To achieve the objective of the study, a consensual and critical review was carried out using both primary sources, such as scientific articles, and secondary sources, such as bibliographic indexes, web pages and databases. The Sustainable Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 181 publications
1
29
0
1
Order By: Relevance
“…Our data suggest that females had higher stress levels during the confinement phase of the COVID-19 pandemic than males, as well as higher levels of anxiety and loneliness. In this line, authors reported similar results, showing that females have a higher perception of danger from COVID-19 and higher values of anxiety, conscientiousness, neuroticism, and openness to experience than males [ 27 ]. This may be explained due to the greater emotional vulnerability of females, as reported by previous authors [ 28 ], and the lower stress coping abilities than males [ 29 ], consequent with previous studies conducted during COVID-19 in females [ 30 ], thus supporting the present results.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Our data suggest that females had higher stress levels during the confinement phase of the COVID-19 pandemic than males, as well as higher levels of anxiety and loneliness. In this line, authors reported similar results, showing that females have a higher perception of danger from COVID-19 and higher values of anxiety, conscientiousness, neuroticism, and openness to experience than males [ 27 ]. This may be explained due to the greater emotional vulnerability of females, as reported by previous authors [ 28 ], and the lower stress coping abilities than males [ 29 ], consequent with previous studies conducted during COVID-19 in females [ 30 ], thus supporting the present results.…”
Section: Discussionmentioning
confidence: 68%
“…Yet, gender-related risk factors for and experiences of burnout and poor mental health remain under-researched and under-reported in the post-pandemic crisis. The educational model change and the return to the traditional model could be an extra stressor for students, being a source of stress that could affect other life aspects, such as personal and interpersonal relations and daily behaviors [ 27 , 42 , 43 , 44 ], and having, in this aspect, information access, a direct effect to modulate the stress perception and a fact that would indirectly affect the educational process [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should not be forgotten how the latest crisis caused by COVID-19 has led nations to reposition themselves in terms of SD (Clemente-Suárez et al, 2022). And, so the international data show it clearly and concisely (Sachs et al, 2022).…”
Section: Conclusionesmentioning
confidence: 99%
“…Various aspects of COVID-19′s influence have been noted in [ 37 ], such as those on livelihoods [ 38 ]; socio-economic issues [ 39 , 40 ]; business, consumption, employment, market [ 41 ]; sustainable development goals [ 42 ]; education [ 43 , 44 ]; tourism and travel [ 41 , 45 , 46 ]; work, workers, remote work [ 45 , 47 ]; environmental implications [ 48 ]; and urban agglomerations [ 49 ], or the exodus towards suburban areas of higher environmental quality [ 50 ], the latter process having begun before the pandemic and gathered pace during COVID-19 [ 45 ].…”
Section: Introductionmentioning
confidence: 99%